THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION: A CASE STUDY ON PASSENGER FERRY ROUTE BATAM-TANJUNG PINANG - Yulinda Tarigan; Putri Malva Ulimaz (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
The purpose of this study is to aimed the effect of service quality, and price have positive effect to customer satisfaction. In addition service quality is measured by five dimensions: tangible, reliability, responsiveness, assurance, empathy, while price is measured by using the fairness indicator of ship ticket price, fair pricing policy, ethical ticket pricing policy, acceptable ticket pricing policy. This study use quesionnaire which is five likert scale. Furthermore, this study used samplingmethod moreover, this study used random samplig technique, Analyzer used is liniear regression analysis and f-test. The results of this study found that service quality has a a positive influence on customer satisfaction, Price has a positive effect on customer satisfaction. This study are used the ferry passenger population of Batam-Tanjung Pinang route, Subsequent research is expected to increase the population becomes more widespread, such as passengers ferry Batam-Tanjung Pinang route and Batam-Tanjung Uban route, and add new variables such as punctuality.